Metaphysical Views on Factors Disturbing Harmony Between Religious Peoples - Rizka Fadillah; Sipra Barutu; Muhammad Fauzan Pratama; Sugeng Pranoto; Sulis Sutiono (Jurnal Scientia, 2025)
Inter-religious harmony is a crucial aspect in maintaining social stability and community harmony in Indonesia. This study discusses the factors that disrupt inter-religious harmony through a metaphysical perspective, specifically by referring to the concept of metaphysics of togetherness from philosopher Gabriel Marcel. The research method used is a literature study that focuses on analysing theories and concepts in various related literatures. The results show that the concept of human relations, namely the ‘I-You’ and ‘I-Ia’ relations, has a significant influence in shaping patterns of social interaction that can support or hinder harmony. Tolerance and the principle of religious freedom are the main factors in realising harmony, supported by philosophical foundations and religious teachings. In addition, factors that disrupt religious harmony include discrimination, differences in interpretation of religious teachings, and political interests that utilise religious issues for certain interests. To overcome these disturbances, an awareness of the importance of the principles of justice, respect for diversity, and an understanding that human life is basically ‘existing together’ with others is needed. This study confirms that building inter-religious harmony requires not only social and legal approaches, but also philosophical awareness of the essence of human existence as interconnected beings.